Sustainability for Innovative Education – The Case of Mobile Learning. Issue 1 (30th October 2015) - Bachmair, Ben; Pachler, Norbert
The successful introduction of mobile learning into education is arguably premised on sustainability in the sense of an ability to maintain innovation over time and to become embedded into mainstream practice. This paper argues that such an endeavour requires a discursive approach, decoupling sustainability from the notion of unambiguity tendentiously inherent in technological paradigms. Learning with mobile devices is an educational response to societal transformation characterized among other things by the detraditionalization of established modes of media and communication in everyday life. Detraditionalization can be seen to refer to the process of breaking down, or challenging, traditional social structures but also encompasses rather more fundamental transformations in the spheres of politics, the economy and culture. In this paper, with particular but not exclusive reference to education, we focus on the tension between established institutions, systems, regulations and practices on the one hand, and emerging forms of teaching and learning afforded by new media and technology on the other. Delimitation (Beck and Lau, 2004 ), a central conceptual perspective discussed in this paper, can be viewed as one consequence of detraditionalization, namely the blurring of previously rigid boundaries (e.g. those pertaining to social class or political certainties). An important conceptual frame for this paper is the mobile complex (Pachler, Bachmair and Cook, 2010 ), which shapes mobile learning and results from the delimitation of structures, agency and practices. In turn delimitation does not lead to new, transformed but stabile features; instead it is characterised by provisionality. Provisionality is an important aspect of the continuous process of detraditionalization, where stable practices, norms and social structures are replaced by perpetually fluid and transient ones. The key issue under consideration here, therefore, is the interdependence of mobile learning and sustainability within societal structures, agency and cultural practices. The paper proposes some operational tools for the discussion and consideration of sustainability of mobile learning under the specific societal conditions of the mobile complex, i.e. the 'new normal' of provisionality.